CORRELATION OF ENVIRONMENTAL FACTORS AND DIATOM ASSEMBLAGES IN AKKESHI-KO ESTUARY SYSTEM - Ma’ruf Kasim (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The correlation between diatoms and environmental factor were studied in Akkeshi-ko estuary, easthern part of Hokkaido, Japan. This studied were aimed to clarify whether the dynamic and distribution pattern can be made by correlating for environmental variation and diatoms assemblages in an estuarine system. During this research, there are  positive correlations between pelagic diatom abundance in water column (PDWC), depth and salinity (r = 0.623 and r = 0.652; respectively). There are positive relationship between nitrite + nitrate and the abundance of diatom on the surface sediment. Seasonal variation of the relationship between abundance of diatoms assemblages and ammonia, nitrite+nitrate and phosphate showed occurs in most stations, the high abundance of benthic and pelagic diatoms in summer followed by the increasing of ammonia, nitrite and nitrate and phosphate.